Unenlagiinae revisited: dromaeosaurid theropods from South América - Gianechini,Federico A. (2011)
Over the past two decades, the record of South American unenlagiine dromaeosaurids was substantially increased both in quantity as well as in quality of specimens. Here is presented a summary review of the South American record for these theropods.Unenlagia comahuensis, Unenlagia paynemili, and Neuquenraptor argentinus come from the Portezuelo Formation, the former genus being the most complete and with putative avian features. Neuquenraptor is more incomplete and exhibits pedal features resembling those of Unenlagia. The earliest and most complete South American dromaeosaurid is Buitreraptor gonzalezoru, whose preserved cranial remains, provides important data in the characterization of unenlagiines. The most recently described,Austroraptor cabazai also with cranial remains, allows further comparisons with Laurasian lineages and a better characterization of unenlagiines. The possible synonymy between nenlagia and Neuquenraptor is discussed. Additional evidences from Brazil and Colombia show that dinosaurs with similar dentition to that of unenlagiines were present in the whole South America. However, it is not possible to discart that these remains may belong to other unknown maniraptoran lineages, considering the increasing number of taxa of this group found in South America.